Correlates of Continued Church Membership Intention: An Empirical Study of Religion in Ghana - Yalley, Andrews Agya (Journal for the scientific study of religion, 2025)
This study examines the factors influencing continued church membership intention in Ghana, focusing on the key correlates of this behavior. Using structural equation modeling (SEM) the survey data collected were analyzed. The findings highlight charismatic leadership, religious experience, corporate social responsibility, personal needs fulfillment, tangibles, and message credibility as significant determinants of continued church membership intention. Furthermore, the study identifies a willingness to donate as a consequential outcome. The proposed integrative model not only offers scholars essential constructs for future theoretical exploration but also provides church managers with a comprehensive framework to enhance membership retention strategies. This research serves as a critical foundation for both academic and practical advancements in understanding the dynamics of church membership.